A retrospective of the spatial development of Yaroslavl region - V. O. Okhotnikov; D. M. Astanin (Архитектура, строительство, транспорт)
The article considers the principles of spatial settlement in the modern territory of the Yaroslavl region, urban planning and the main social and economic factors inﬂuenced the development of regional cities. From the second half of the 11th century in Russia intensiﬁed the tendency of building towns along the banks of rivers and lakes, and this one determined the peculiarities of urban planning of the region. Cities of Yaroslavl region were characterized by fan layout. During several ﬁrst ﬁve-year plans Yaroslavl became one of the main industrial centers of the country. The current strategy of social and economic development of Yaroslavl region is aimed at strengthening small and medium-sized cities, taking advantage of the proximity to Moscow agglomeration.